BCL10 aberations and NF-kappa B activation involving p65 are absent or rare in primary gastric MALT lymphoma - Hajder, Jelena; Marisavljević, Dragomir; Stanisavljević, Nataša; Mihaljević, Biljana; Kovčin, Vladimir; Marković, Olivera; Živković, Radmila (Vojnosanitetski pregled, 2014)
Bacground/Aim. Mucosa-associated lymphoid tissue (MALT) lymphoma accounts for 5–17% non-Hodgkin lymphomas (NHL). The molecular pathogenesis of MALT lymphomas is not well-established. The aim of this study was to evaluate immunohistochemically determined nuclear coexpression of BCL10 and NF-kappaB (NF-κB) in tumor cells of gastric MALT lymphoma and its impact on the patogenesis and outcome of the disease. Methods. Medical records of 35 patients with newly diagnosed gastric MALT lymphoma were analyzed and biopsy specimens were immunostained for BCL10 and NF-kB expression (p65 subunit). Results. The median age of 35 patients diagnosed with gastric MALT lymphoma was 63.5 years (male/female = 21/14). Symptoms were present in 23/35 (65.7%) patients with the weight loss as the most common symptom. Gastric MALT lymphomas were usually localized in the stomach corpus and corpus and antrum (45.7% and 31.2%, respectively). H. pylori infection was confirmed in 20 out of 30 (66.7%) patients. Treatment options were as follows: immunochemotherapy in 10 (28.5%) patients, surgery in 9 (25.8%) patients, combined surgery and chemotherapy in 14 (40%) patients and supportive measures in 2 (5.7%) patients. Complete remission was achieved in 13 (37.1%) patients and partial remission in two (5.7%) patients. Sixteen (45.7%)  patients had disease progression (p
Keywords: lymphoma; b-cell; marginal zone; stomach neoplasms; immunohistochemistry; gene expression; signal transduction